2021
DOI: 10.3389/fonc.2021.667843
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Tumorigenesis and Metabolome in Male Adipose Specific Monocyte Chemotactic Protein-1 Deficient MMTV-PyMT Mice Fed a High-Fat Diet

Abstract: Male breast cancer, while uncommon, is a highly malignant disease. Monocyte chemotactic protein-1 (MCP-1) is an adipokine; its concentration in adipose tissue is elevated in obesity. This study tested the hypothesis that adipose-derived MCP-1 contributes to male breast cancer. In a 2x2 design, male MMTV-PyMT mice with or without adipose-specific Mcp-1 knockout [designated as Mcp-1-/- or wild-type (WT)] were fed the AIN93G standard diet or a high-fat diet (HFD) for 25 weeks. Mcp-1-/- mice had lower adipose Mcp-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…57,58 The notion that the HFD accelerates glycolysis in LLC-bearing mice is supported by findings from a recent metabolomic comparison in which elevated glucose and decreased 1,5-anhydroglucitol occur in plasma from MMTV-PyMT mice fed a HFD. 18 In the present study, we observed elevations of citric acid, fumaric acid, isocitric acid, succinic acid, and glyceric acid in Mcp-1 -/mice regardless of the diet. Furthermore, the network analysis showed alteration in the citrate cycle pathway when compared Mcp-1 -/mice to WT mice.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…57,58 The notion that the HFD accelerates glycolysis in LLC-bearing mice is supported by findings from a recent metabolomic comparison in which elevated glucose and decreased 1,5-anhydroglucitol occur in plasma from MMTV-PyMT mice fed a HFD. 18 In the present study, we observed elevations of citric acid, fumaric acid, isocitric acid, succinic acid, and glyceric acid in Mcp-1 -/mice regardless of the diet. Furthermore, the network analysis showed alteration in the citrate cycle pathway when compared Mcp-1 -/mice to WT mice.…”
Section: Discussionsupporting
confidence: 59%
“…39 In the present study, the decreased valine in Mcp-1 -/mice, particularly those fed the HFD, is consistent with a recent metabolomic analysis showing that plasma level of valine is lower in adiposespecific Mcp-1 deficient MMTV-PyMT mice. 18 Taken together, these findings indicate that the inflammatory cytokine MCP-1 may modulate BCAA metabolism pathways in cancer-bearing mice. Elevations of plasma serine and glycine in mice fed the HFD indicate that the HFD may alter serine and glycine metabolism in LLC-bearing mice.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…6,8,11,12 In contrast, male MMTV-PyMT mice display a delayed onset of tumor growth with lower penetrance of metastasis, resembling tumor growth profiles in men, which develop 5 to 10 years later than in women. 13 Gene expression profiling has revealed that PyMT mouse breast tumors model the luminal B molecular subtype of human breast cancer, with overexpression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (Her2/neu). 9,10,13 Overall, these observations reinforce that tumor progression in female and male PyMT mice recapitulates the complex stages and heterogeneity of breast cancer in humans.…”
Section: Introductionmentioning
confidence: 99%